The Prometheus Man : Prometheus Man #1 - Reardon, Scott (New York : Mulholland Books, 2016)
A young CIA agent's identity is stolen by a gifted college drop-out who would use agency resources to solve the cold case of his brother's murder, a situation that is complicated by a secret government program to engineer a perfect soldier.
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; Spy fiction; Suspense fiction